CONSIDERATION OF SOCIAL SEMIOTICS IN THE SELECTION OF LEARNING MATERIAL AS PRINTED-BASED LITERACY FOR ELT TEACHER IN 21ST CENTURY SKILL - Vina Fathira; Diana Zuriati (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Social semiotics is the study of a group of objects, events, culture, and so on in society as a sign with a specific meaning. This is extremely beneficial when it comes to the selection and production of educational materials in schools for 21st century skill. This study aims to describe the urgency of social semiotic considerations in the selection of learning material as printed-based literacy in English language teaching in schools for 21st century skill. This study used a qualitative method research. The subjects of this study were English language teachers in Riau. The data obtained in the form of the results of filling out a questionnaire in the form of choices and short answers in accordance with the objectives of this study. The data collection technique used is a questionnaire via Google form. This study uses qualitative in analyzing the data obtained. Based on this research, the researcher found that the need for consideration of social semiotics in the selection of learning material as printed-based literacy in English language teaching is very necessary. The biggest difficulty is applying social semiotics as a way of making learning material as printed-based literacy in learning English later. However, the textbook still does not use social semiotics learning material as printed-based literacy in English learning. Therefore, the six language components in social semiotics are needed. With the existence of the six language components in the study of social semiotics, it is hoped that teachers will find it easier to select and make learning material as printed-based literacy in the school environment